Characteristics of polyol ester as transformer insulating oil - Abdul Raof, Nurliyana (2021)
Mineral-based transformer oil has long served the purposes of insulating and cooling in an electrical power transformer. However, its low flash and fire point constitute a high risk for fire and explosion and not suitable to be used in densely-populated and environmentally sensitive areas. The overall objective of this study is to develop an environmentally friendly polyol ester that is practical and suitable for the transformer application. Specifically, the effect of polyol esters with different chemical structures on the electrical properties and oxidative degradation were investigated. Different chemical structures that can be produced from the transesterification of various methyl esters (C8/C10, C12 and C18) with neopentylglycol (NPG)/ trimethylolpropane (TMP) alcohols were synthesized and compared with those of commercial synthetic ester PFAE and mineral oil. Based on the evaluation of physicochemical and electrical properties, TMPE C18 exhibited the most optimum insulation properties with excellent flash point and moisture content, excellent breakdown voltage, relative permittivity, dissipation factor and resistivity. Experimental investigations on the oxidative characteristics and catalytic effects of copper/iron on different esters were also conducted by using the turbine oil oxidation test (TOST). The unadditived TMPE C18 ester showed a comparable oxidative performance to the commercial ester PFAE and the most viable option for ester-based transformer oil. TMPE C18 exhibited high stability against oxidation by having almost similar oxidation lifetime as PFAE, maintains low acidity even after oxidation duration and does not corrode copper or iron. The effects of different ester and mineral oil blending composition were further investigated to improve the current properties of base oil. C18 TMPE sample was blended and homogenized with 20 to 50% of mineral oil. It was found that the 20MO (80/20 of C18 TMPE/mineral oil) blending sample has the properties near to the standard values for transformer liquid insulation. The effects of different antioxidants were studied too. Blends containing Irganox L57 antioxidant showed a remarkable oxidation lifetime compared with other antioxidants. However, the use of Irganox L57 contributed to increased concentration of copper and iron after oxidation in oil thus gives comparable performance to untreated 20MO blend. The thermal aging behavior of insulating paper aged in unadditived 20MO blend at 110, 130 and 150°C for 14, 28, 42, 56 and 84 days were evaluated and compared with that of mineral oil. The overall results showed that paper aged in mineral oil degraded significantly faster than in the 20MO blend. The kinetics study on the Kraft paper degradation predicted the loss of tensile strength and degree of polymerization aged in blend and mineral oil and the proposed kinetics model fitted well with the experimental data. The blend showed good thermal ageing characteristics compared to the conventional mineral oil.